Consumption of Pineapple Juice to Accelerate Uterine Involution in Postpartum - Ratna Ningsih; Maliha Amin; Prahardian Putri; Imelda Erman (Universitas Muhammadiyah Semarang, 2023)
Post delivery occurs the pelvic wall was always stretched/damaged in the birth canal, and the pelvic floor muscles are loose, hence the implementation of accelerated uterine involution with the consumption of pineapple juice. The purpose identified the effect of pineapple juice consumption on the acceleration of uterine involution in postpartum. This research uses a quasi-experiment with posttest only with a control group design. The sample of 34 was taken in consecutive sampling. How to measure observations and questionnaires, as well as analysis using chi-square tests. Results: The entire intervention group of rapid uterine involution processes, while in the slow control group. The results of the Chi-Squre test obtained p value = 0.000 means there is an influence of pineapple juice consumption on the acceleration of uterine involution in postpartum mothers. Pineapple juice's ability to lower TFU is related to the content of the enzyme Bromelain which increases hydrolytic activity in connective tissue, especially against collagen. The activity of bromelain collagenase by hydrolyzing collagen causes the uterine wall to become soft and connective tissue to tighten, accelerating uterus involution. Consumption of pineapple juice has an effect on accelerating uterine involution.